Tourists perception of the safe city programme in Kuala Lumpur / Sharina Abd Rahim - Abd Rahim, Sharina (2013)
Kuala Lumpur is one of the top destinations for international tourists. However, it is also one of the notorious urban destinations in Malaysia and had been identified as one of the hot spots for crime. As a result of this, a comprehensive approach in reducing crime was highlighted in the Government Transformation Programme (2010). Among the approaches that were introduced is the Safe City Programme (SCP). The SCP is beneficial in promoting urban tourism as safety is a highly considered factor for choosing a destination. Therefore, this study was undertaken to investigate the tourists perception of the SCP in increasing their feeling of safe in Kuala Lumpur. A survey involving 170 international tourists was carried out. Findings reveal that tourists were not aware of the SCP, however, they are aware of the measures under the SCP. Moreover tourists feel much safer with the presence of police, CCTV and good lighting. The study also reveals that tourists do feel safe and are satisfied with the safety in Kuala Lumpur. In light of the findings, it is recommended that the measures under the SCP should be promoted as it could be one of the pull factors for international tourists to visit Kuala Lumpur.